On the Hochstadt-Lieberman theorem for discontinuous boundary-valued problems - Wang, Yu Ping; Koyunbakan, Hikmet (Springer Heidelberg, 2014)
In this paper, we discuss the half inverse problem for Sturm-Liouville equations with boundary conditions dependent on the spectral parameter and a finite number of discontinuities inside the interval and prove the Hochstadt-Liberman type theorem for the above boundary-valued problem.
Keywords: Half inverse problem; Sturm-Liouville operator; potential; interior discontinuity; boundary condition dependent on the spectral parameter